2004
DOI: 10.1007/s00221-004-1905-2
|View full text |Cite
|
Sign up to set email alerts
|

When two eyes are better than one in prehension: monocular viewing and end-point variance

Abstract: Previous research has suggested that binocular vision plays an important role in prehension. It has been shown that removing binocular vision affects (negatively) both the planning and on-line control of prehension. It has been suggested that the adverse impact of removing binocular vision is because monocular viewing results in an underestimation of target distance in visuomotor tasks. This suggestion is based on the observation that the kinematics of prehension are altered when viewing monocularly. We argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 23 publications
10
72
0
Order By: Relevance
“…2 A). This result confirms previous observations (Jackson et al, 1997;Bradshaw and Elliott, 2003;Loftus et al, 2004) and corroborate the sensitivity of the behavioral measures acquired during MR scanning. Crucially, GRASP time was not influenced by the object slant, excluding the possibility that orientationrelated cerebral effects could be a by-product of behavioral differences.…”
Section: Behavioral Effectssupporting
confidence: 92%
“…2 A). This result confirms previous observations (Jackson et al, 1997;Bradshaw and Elliott, 2003;Loftus et al, 2004) and corroborate the sensitivity of the behavioral measures acquired during MR scanning. Crucially, GRASP time was not influenced by the object slant, excluding the possibility that orientationrelated cerebral effects could be a by-product of behavioral differences.…”
Section: Behavioral Effectssupporting
confidence: 92%
“…Specifically, does the additional 3D scene and object information provided by binocular vision (e.g., from vergence and disparity; Mon-Williams and Dijkerman 1999; Bradshaw et al 2004;Melmoth et al 2007;Anderson and Bingham 2010) afford greater efficiencies for obstacle avoidance and, hence, lower the risk of collision, compared to the less 'certain', reduced-3D-cue conditions of monocular viewing? Given that binocular advantages have been repeatedly demonstrated for movement execution (increased speed, accuracy and precision) when normal adults are required to grasp objects presented in isolation (e.g., Servos et al 1992;Servos and Goodale 1994;Watt and Bradshaw 2000;Bradshaw and Elliot 2003;Loftus et al 2004;Melmoth and Grant 2006), the likely answer would seem to be 'yes'. This conjecture is supported by the fact that the normal 'automaticity' of obstacle avoidance is contingent on intact dorsal stream-posterior parietal cortical functioning Schindler et al 2004;Rice et al 2006), probably involving areas with privileged access to binocular 3D (e.g., near-space, absolute and dynamic disparity) information useful for hand movement programming and on-line guidance (Quinlan and Culham 2007;Verhagen et al 2008Verhagen et al , 2012Gallivan et al 2009;Srivastava et al 2009;Cottereau et al 2012).…”
Section: [Figure 1 Near Here]mentioning
confidence: 99%
“…Performance was faster, more accurate and less variable when binocular vision was available for evaluating the scene and assembling the motor plan during the initial preview and for grasping the isolated target (c.f., Servos et al 1992;Watt and Bradshaw 2000;Loftus et al 2004;Melmoth and Grant 2006). Indeed, there are potential advantages of two eyes over one for each of these processes, from access to extra binocularly-specific depth cues for more reliable statistical encoding of the target's 3D location and intrinsic properties (Landy et al 1995;Keefe and Watt 2009) -to which the visuomotor system seems to attach a greater weighting during the formulation of appropriate motor responses (Knill 2005;Makris et al 2013) -to their increased efficiency in mediating feedback for correcting movement errors on line (Servos and Goodale 1994;Jackson et al 1997;Bradshaw and Elliot 2003;Greenwald et al 2005).…”
Section: Does the Additional 3d Information Provided By Binocular Vismentioning
confidence: 99%
“…Tangential speed thresholds of 20 mm/s was used to mark the beginning and end points of the wrist movements, respectively (e.g., Loftus et al, 2004). 4 Other spatial components of the grasp have been considered in the literature, such as peak grip aperture and peak grip velocity, and it has been shown that these different variables produce a very similar pattern of results (see Gentilucci, Benuzzi, Gangitano, & Grimaldi, 2001;Jakobson & Goodale, 1991;Jeannerod, 1984;1988;Servos, Goodale, & Jakobson, 1992).…”
Section: Test For Hypothesis H1mentioning
confidence: 99%